IMPLEMENTASI DECISION SUPPORT SYSTEM UNTUK PENENTUAN LOAN CREDIT SCORE DENGAN MENGGUNAKAN METODE TOPSIS (Studi Kasus: BFI Finance BSD Tanggerang) - Asep Yudistira Saputra; Hadi Zakaria (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The oldest lending company in Indonesia is PT BFI Finance Indonesia Tbk ("BFI" or the "Company"), which was established in 1982 under the name PT Manufacturer Hanover Leasing Indonesia. BFI Finance has established itself as a leader in this sector throughout the course of its lengthy history. Regarding the issues at PT. BFI Finance, calculating loan credit scores effectively and precisely is difficult since it takes into account a number of variables, including income, credit history, and other risk indicators. As a result, risk credit scores are accurately determined when evaluating BFI Finance's lending viability. By taking into account the relative proximity to the ideal solution and the ideal negative solution, the TOPSIS approach makes it possible to choose the optimal option among several options. This approach can more reliably and accurately calculate credit scores by utilizing past data and pertinent borrower attributes. It is anticipated that this implementation will lower credit risk, boost confidence in financial institutions, and improve the accuracy of determining borrower eligibility. In addition, a more effective decision-making process can lower operating expenses and boost productivity. Users can gather pertinent borrower data, including income, credit history, and collateral details, by creating the appropriate database structure. with the use of MySQL and PHP scripts. A borrower's credit score can be determined using the TOPSIS approach. By using the TOPSIS method, this study significantly enhances BFI Finance's operational effectiveness and service quality, which helps the organization become more accurate in its evaluations.